2020
DOI: 10.1186/s12967-020-02465-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Sars-Cov-2 threaten our dreams? Effect of quarantine on sleep quality and body mass index

Abstract: Background: COVID 19-related quarantine led to a sudden and radical lifestyle changes, in particular in eating habits. Objectives of the study were to investigate the effect of quarantine on sleep quality (SQ) and body mass index (BMI), and if change in SQ was related to working modalities. Materials: We enrolled 121 adults (age 44.9 ± 13.3 years and 35.5% males). Anthropometric parameters, working modalities and physical activity were studied. Sleep quality was evaluated by the Pittsburgh Sleep Quality Index … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
93
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 60 publications
9
93
1
4
Order By: Relevance
“…In Italy, cross-sectional investigations have suggested that while the number of hours spent in bed might have increased during lockdown [ 2 ], many individuals reported insomnia (43%) [ 19 ] and poor sleep quality (57%) [ 9 ]. Similar percentages of sleep deterioration (48%) were also shown in the UK [ 20 ], and a longitudinal study conducted in Italy confirmed the detrimental effects of the 40-day lockdown on all the parameters of the Sleep Quality Index [ 21 ], except for sleep duration [ 22 ]. Our cohort seems to confirm that sleep quality deteriorated during lockdown, as among those individuals who experienced a change in their sleep quality, 85.8% defined their sleep as poor.…”
Section: Discussionsupporting
confidence: 53%
“…In Italy, cross-sectional investigations have suggested that while the number of hours spent in bed might have increased during lockdown [ 2 ], many individuals reported insomnia (43%) [ 19 ] and poor sleep quality (57%) [ 9 ]. Similar percentages of sleep deterioration (48%) were also shown in the UK [ 20 ], and a longitudinal study conducted in Italy confirmed the detrimental effects of the 40-day lockdown on all the parameters of the Sleep Quality Index [ 21 ], except for sleep duration [ 22 ]. Our cohort seems to confirm that sleep quality deteriorated during lockdown, as among those individuals who experienced a change in their sleep quality, 85.8% defined their sleep as poor.…”
Section: Discussionsupporting
confidence: 53%
“…An increase in children’s body weight was declared by 32% of the respondents. Other authors reported similar changes both in pediatric [ 57 ] and in adult [ 58 , 59 , 60 , 61 ] populations since the beginning of the restrictions due to the pandemic. A study analyzing the Google Trends covering a timeframe from June 2019 to April 2020 revealed that people have replaced outdoor activities with sedentary indoor behaviors [ 62 ].…”
Section: Discussionmentioning
confidence: 56%
“…These changes in lifestyle render weight gain and increase the risk of developing obesity. 3,4 Here we reviewed the impact of obesity in COVID- 19. This paper will provide a comprehensive understanding on the role of obesity in the pathogenesis of COVID-19 and provide suggestions on the clinical management of COVID-19 in obese patients.…”
Section: Introductionmentioning
confidence: 99%